English for Medical Purposes: An Investigation into Medical Students’ English Language Needs - Nargess Hekmati; Mohammad Davoudi; Gholamreza Zareian; Mahmoud Elyasi (Iranian Journal of Applied Language Studies, 2020)
This study aims at investigating the Medical students’ English language needs as the first step for designing an alternative curriculum for teaching English for Medical Purposes (EMP). It also tries to examine if the needs of medical students are perceived differently by stakeholders in medical sciences. For so doing, a structured questionnaire was developed and distributed among 282 Medical Students, 12 instructors, and 15 practitioners studying and working at Birjand University of Medical Sciences, Iran. The collected data were analyzed by SPSS using statistical tests of Mann-Whitney U and Kruskal-Wallis. The findings indicated that medical students need to be competent enough in all four language skills, considering the demanding nature of their profession in the future. They ranked the importance of language skills like reading, writing, speaking, and listening, respectively. Besides, the results of four Kruskal-Wallis tests indicated a statistically significant difference among the responses of the three groups regarding the importance of the subcomponents of speaking and listening skills. Six follow-up post hoc analyses showed that the differences lay between medical students and practitioners. The findings are discussed and the implications for policy and practice are made.